Quantitative Evaluation of High-quality Grain Project Policy Based on PMC Index Model - CUI Ning-bo; SONG Rui; LAN Hui; FAN Yue-yuan (Liang you shipin ke-ji)
The high-quality grain project serves as the most direct and effective approach to promote the high-quality development of grain industry. This paper constructs a three-dimensional analysis framework of “policy subject-policy instrument-policy effectiveness”, and comprehensively applies methods such as bibliometric analysis, content analysis, PMC index model and other research methods to conduct quantitative evaluation of 56 high-quality grain project policies from 2017 to 2023. The findings are as follows: 1) The primary entities of the policy have gradually established a trend of "focusing on the central and local food departments and cooperating with multiple departments". 2) The use of high-quality grain project policy tools is relatively coordinated, and the overall preference pattern is "supply > environment > demand". 3) The average score of PMC index score for 10 representative policy contents is 6.56 indicatinggood overall performance, however there remains room for improvement in areas such as safeguard measures. Based on this, the policy optimization suggestions are put forward.